A large moradisaurine tooth plate from the Lower Permian of Texas and its biostratigraphic implications. Issue 6 (1st November 2016) - Modesto, Sean P.; Flear, Vonica J.; Dilney, Melissa M.; Reisz, Robert R.
SUPPLEMENTAL DATA: Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Modesto, S. P., V. J. Flear, M. M. Dilney, and R. R. Reisz. 2016. A large moradisaurine tooth plate from the Lower Permian of Texas and its biostratigraphic implications. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2016.1221832.